2019
DOI: 10.20546/ijcrbp.2019.603.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic identification of viruses affecting pepper crop (Capsicum spp.) in Western North of Benin

Abstract: A. A. Fanou et al. (2019) / Molecular genetic identification of viruses affecting pepper crop (Capsicum spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Polymerase chain reactions (PCR) were performed to identify resistance gene(s) among the selected accessions. Six co-segregating STS markers tightly linked to xa5, Xa7, xa13, and Xa21 [26][27][28][29] were used (Table 3) for the detection of bacterial blight-resistant gene(s). Amplification was carried out in a thermal cycler according to the following programme: pre-denaturation at 95°C for 5min followed by 35 cycles consisting of denaturation at 94°C for 1min, hybridisation at 51°C (for the RM122 marker), 59°C (for the M5 and xa13-prom markers), 55°C and 57°C (for the pTA248 marker) for1min, elongation at 72°C for 2min and final extension at 72°C for 5min.…”
Section: Molecular Screening Of Rice Accessions Cultivated In Benin F...mentioning
confidence: 99%
“…Polymerase chain reactions (PCR) were performed to identify resistance gene(s) among the selected accessions. Six co-segregating STS markers tightly linked to xa5, Xa7, xa13, and Xa21 [26][27][28][29] were used (Table 3) for the detection of bacterial blight-resistant gene(s). Amplification was carried out in a thermal cycler according to the following programme: pre-denaturation at 95°C for 5min followed by 35 cycles consisting of denaturation at 94°C for 1min, hybridisation at 51°C (for the RM122 marker), 59°C (for the M5 and xa13-prom markers), 55°C and 57°C (for the pTA248 marker) for1min, elongation at 72°C for 2min and final extension at 72°C for 5min.…”
Section: Molecular Screening Of Rice Accessions Cultivated In Benin F...mentioning
confidence: 99%
“…since previous studies have identified a sequence of approximately 270 Pb which corresponds to a sequence specific to Sphingomonas sp. The technique used is based on the PCR protocol described by Fanou et al[27]. PCR was performed using a thermal cycler in 20 µL volumes containing a mixture of 1 × PCR buffer, 0.1 mM dNTPs, 0.2 μM each of forward and reverse primers, 50 -200 ng genomic DNA, 2.0 -3.0 U of Taq DNA polymerase, with sterilized distilled water added to 50 μL.…”
mentioning
confidence: 99%